Three-dimensional oropharyngeal airway changes after facemask therapy using low-dose computed tomography: a clinical trial with a retrospectively collected control group - Amr H. Husson; Ahmad S. Burhan; Mohammad Y. Hajeer; Fehmieh R. Nawaya (SpringerOpen, 2021)
Abstract Aims This study aimed to evaluate the short-term oropharyngeal airway volumetric changes in growing Class III maxillary-deficient patients treated by facemask without expansion compared with untreated Class III controls, using low-dose computed tomography. Methods Eighteen maxillary-deficient children (9 boys, nine girls) with a mean age of 7.81 ± 0.84 years were treated with maxillary bonded bite block and facemask (FM). Pre- (T1) and post-treatment (T2) low-dose CT images were acquired. Sixteen untreated Class III patients with a mean age of 7.03 ± 0.56 years had previously two low-dose CT scans within a one year of follow-up. Volumetric and minimal cross-sectional area measurements were obtained to assess the oropharyngeal airway changes. Quantitative mean, minimum, and maximum displacement of superimposed 3D models were estimated from a point-based analysis. Paired-samples t-tests were used for the intragroup comparisons, and an independent samples t-test and the Mann-Whitney U tests were carried out for the intergroup comparisons. Results A statistically significant increase in the total and retropalatal volumes oropharyngeal airway volume were observed in the control group (302.23 ± 345.58 and 145.73 ± 189.22 mm3, respectively). In the FM group, statistically significant increases in the total and retropalatal volumes were observed (738.86 ± 1109.37 mm3 and 388.63 ± 491.44 mm3, respectively). However, no statistically significant differences were found between the two groups, except for the maximum part analysis which was significantly greater in the FM group (p = 0.007). Conclusions FM therapy appeared to have no additional effects on the oropharyngeal airway other than those induced by growth.